Recent Advances in Paper-Based Electronics: Emphasis on Field-Effect Transistors and Sensors - Dimitris Barmpakos; Apostolos Apostolakis; Fadi Jaber; Konstantinos Aidinis; Grigoris Kaltsas (Biosensors)
Paper-based electronics have emerged as a sustainable, low-cost, and flexible alternative to traditional substrates for electronics, particularly for disposable and wearable applications. This review outlines recent developments in paper-based devices, focusing on sensors and paper-based field-effect transistors (PFETs). Key fabrication techniques such as laser-induced graphene, inkjet printing, and screen printing have enabled the creation of highly sensitive and selective devices on various paper substrates. Material innovations, especially the integration of graphene, carbon-based materials, conductive polymers, and other novel micro- and nano-enabled materials, have significantly enhanced device performance. This review discusses modern applications of paper-based electronics, with a particular emphasis on biosensors, electrochemical and physical sensors, and PFETs designed for flexibility, low power, and high sensitivity. Advances in PFET architectures have further enabled the development of logic gates and memory systems on paper, highlighting the potential for fully integrated circuits. Despite challenges in durability and performance consistency, the field is rapidly evolving, driven by the demand for green electronics and the need for decentralized, point-of-care diagnostic tools. This paper also identifies detection strategies used in paper-based sensors, reviews limitations in the current fabrication methods, and outlines opportunities for the scalable production of multifunctional paper-based systems. This review addresses a critical gap in the literature by linking device-level innovation with real-world sensor applications on paper substrates.